(untitled) (The International Journal for Scientific Research, 2026)
This study aims to analyze the spatial changes in land use in Al Bahah during the period (2020–2025) and predict future land-use patterns for the year 2030 using remote sensing and Geographic Information Systems (GIS) techniques. Landsat satellite imagery was utilized, and a supervised classification approach was applied to extract land cover categories, including vegetation cover, urban areas, water bodies, and vacant lands. Classification accuracy was evaluated using a confusion matrix and various accuracy indicators to ensure the reliability of the results. The study relied on a transition matrix to analyze change trends among the different categories. The results revealed a significant increase in urban areas accompanied by a decline in vegetation cover, along with varying changes in water bodies and vacant lands. Change rates were also calculated, indicating that urban areas recorded the highest growth rate during the study period, reflecting the accelerating urban expansion in the city. For prediction purposes, the Markov model was implemented through the Google Earth Engine platform to estimate future changes for 2030. The results indicated the continuation of the urban expansion trend, with urban areas expected to reach approximately 91 km², while vegetation cover is projected to decline to about 72 km². Water bodies are also expected to decrease to nearly 17 km², whereas vacant lands are anticipated to remain relatively stable. The findings confirm that Al Bahah is experiencing an increasing pattern of urban sprawl at the expense of natural resources, highlighting the importance of adopting sustainable urban planning strategies that balance urban development with environmental conservation. The study also demonstrates the significance of spatial analysis techniques and predictive models in supporting decision-making and achieving sustainable development.